1998
DOI: 10.1007/s004649900584
|View full text |Cite
|
Sign up to set email alerts
|

How often might a trans–cystic-duct stone extraction be feasible?

Abstract: Physical conditions allowing a trans-cystic-duct stone extraction were present in 23 of 30 patients and an attempt might have been possible after, for example, cystic duct dilatation in a further five.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…OPBR was also present in most patients operated on for other benign gallbladder diseases (Table II). These results support previously published findings [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and additionally confirm that OPBR could play an important role in the development of biliary pathology and associated symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…OPBR was also present in most patients operated on for other benign gallbladder diseases (Table II). These results support previously published findings [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and additionally confirm that OPBR could play an important role in the development of biliary pathology and associated symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…The average number of stones extracted per patient in this series was 7.5 ± 11.8 (range 1-70), and the average size of the stones was 11.5 ± 4.8 (range, mm. This is again in variance with the western reports where the majority of patients have a low stone load with small stone size, making the TC route feasible [30][31][32][33]. The few Asian series that have been published have data similar to the present series with large stone size, higher stone load, and dilated CBDs [9][10][11].…”
Section: Discussionsupporting
confidence: 50%
“…In our series, only four patients were managed through the TC route. Moreover, the stones are large and often impacted and, therefore, are difficult to extract using balloon catheter, unlike in western countries, where it is one of the main methods of stone retrieval [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic transcystic CBD exploration and clearance of the bile duct has been reported to be successful in 70% to 84% of all patients in whom it is attempted 19,22,23. Vracko and Wiechel24 reported that physical conditions allowing a transcystic stone extraction were present in 23 of 30 patients, and an attempt might have been possible after cystic duct dilatation in a further 5 patients. Lezoche et al20 reported that anatomical situations which made transcystic CBD exploration impossible were encountered in approximately one‐third of the patients, e.g., the cystic duct joining the CBD on its medial aspect, a low junction with the CBD, and multiple large stones filling the CBD.…”
Section: Discussionmentioning
confidence: 99%